Penile and scrotum entrapment by a metal ring with pressure sore formation: a clinical case report - S. V. Popov; I. N. Orlov; T. M. Topuzov; E. A. Grin; I. S. Pazin; M. A. Kotlov; A. R. Orlov; N. I. Dub; R. R. Tumenev (Вестник урологии)
Penile entrapment is a rather rare pathology and requires urgent treatment to preserve the organ function. The article presents a clinical case of entrapment of the penile root and scrotum by a metal ring with tissue changes like a pressure sore directly under the ring. Possible methods of emergency surgical treatment in this urgent situation are discussed.